DEGRADATION CAPABILITY AND PRODUCTION OF BIOSURFACTANTOF CRUIDE OIL-DEGRADING BACTERIA FROM SEDIMENTSELAT BARU - Miptahul Huda Wassyukur; Nursyirwani Nursyirwani; Dessy Yoswati (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Petroleum pollution can originiate from oil spills during drilling, production, refining and transportation activities. One of the hardly to decomposed petroleum contaminants is hydrocarbons, once thehydrocarbons enter the marine environment, the chemical componend can be reduced by biological processes (bioremediation) using bacteria. The purpose of this study was to examine the ability of bacterial isolates from Selat Baru coastal sediments to degrade crude oil and produce biosurfactants. This research was conducted in August to October 2018. The ability of bacterial isolates to degrade oil and biosurfactant production was carried out in the Marine Microbiology Laboratory and Marine Chemistry Laboratory, Department of Marine Sciences, Faculty of Fisheries and Marine, University of Riau. Experimental method was used in this research.. Nine isolates of crude oil degrading bacteria were provided from previous researchers, namely isolates 11p31 (1A), 33p31 (3A), 22p41 (10A), 22p42 (4B), 33p31 (5B), 12p32 (9B), 22p31 (1C), 11p41 (9C), 31p41 (12C). Each isolate was examined the ability to degrade crude oil at concentration of 1% (0.5 ml), 2% (1 ml) and 3% (1.5 ml). The highest crude oil degradation ability was at 1% concentration by isolates 22p41 (10A) and 11p41 (9C), and for 2% concentrations by isolates 33p31 (5B) and 3% concentrations by bacterial isolates 33p31 (3A). All bacterial isolates were found to produce biosurfactan through the Oil Speading Assay. Emulsifikation test using kerosene indicated kerosene. where the highest emulsification in test 1 is isolate 33p31 (3A). Then in test 2 the highest emulsification value was shown by isolate 33p31 (3A). In Test 3 the highest emulsification value was isolate 11p41 (9C). Key words:(1)Oil pollution,(2)Degrading,(3)Cruide oil,(4)Biosurfactan,(5)Emulsification